Ensuring Justice in Child Support After Divorce: A Jurimetric Review of at Religious Court of Demak Decision - ahmad nafhani; Irma Suriyani; Gusti Fadhil Fithrian Luthfan; Atik Dina Nasikhah (Jurnal Hukum dan Peradilan, 2025)
Child support is a fundamental right ensuring a child's welfare even after the parents' divorce. In Indonesia, the father is legally obligated to provide both retroactive child support (madhiyah) and prospective child support. However, in practice, the enforcement of these obligations remains inconsistent, and the absence of objective instruments in determining the amount of support creates disparities and weakens the protection of children's rights. This study aims to analyze how judges at the Court of Demak interpret and apply the law regarding retroactive and prospective child support). Using a normative juridical method supported by jurimetric analysis, this research finds that the Religious Court of Demak’s decision concretely guarantees both types of child support through measurable instruments. Retroactive maintenance is determined using a historical audit model based on proven expenses, while prospective maintenance applies a dynamic projection model adjusted to inflation. The decision demonstrates a progressive judicial effort to ensure objective justice, accountability, and long-term legal protection for children within Indonesia’s family law system.